PENGARUH PENERAPAN MODEL MEANINGFUL LEARNING BERBASIS ADVACE ORGANIZER TERHADAP PEMAHAMAN KONSEP PECAHAN KELAS VI SISWA SEKOLAH DASAR - Ihda Malihatun Nisa; Rida Fironika Kusumadewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary school plays an essential role in developing students’ logical, analytical, and conceptual thinking skills, particularly in fraction topics that are abstract in nature. However, in practice, fraction learning is still dominated by procedural memorization, causing students’ conceptual understanding to remain underdeveloped. This study aims to examine the effect of the meaningful learning model based on advance organizers assisted by fraction flower media on students’ understanding of basic fraction concepts in Grade VI of SD Negeri Gabahan. This research employed a quantitative approach using a pre-experimental one group pretest–posttest design. The research subjects consisted of 14 sixth-grade students selected through a saturated sampling technique. Data were collected through pretest and posttest essay tests, teacher interviews, and classroom observations. Data analysis was conducted using the Shapiro–Wilk normality test and the Paired Sample t-test with SPSS. The results showed an increase in the average score of students’ conceptual understanding from 51.60 in the pretest to 72.67 in the posttest. The Paired Sample t-test results indicated a significance value of 0.000 < 0.05, demonstrating a significant effect of the meaningful learning model based on advance organizers on students’ fraction concept understanding. These findings indicate that learning which connects students’ prior knowledge with new information through concrete visual representations can promote deeper and more meaningful conceptual understanding, in line with the principles of deep learning in mathematics education.